Pembelajaran Akidah Akhlak Menggunakan Media Film Animasi Syamil dan Dodo - Rini Supartiana (Jurnal Dewantara, 2018)
The cultivation of akhlakul karimah is done through the learning process of Aqidah Akhlak in Madrasas. Akidah Akhlak Learning is one of the lessons in the subjects of religious groups that instill morals in students. For smooth implementation, a learning can not be separated from a learning media which is one of the important supporting components in determining the success of learning. Media is used to facilitate teachers in channeling what they want to distribute and make it easier for students to understand the goals that the teacher wants to channel. The type of learning media that will be used in learning Akidah Akhlak is an animated film media. Film Animation Media is used as a liaison or channeling material to be conveyed to students. The implementation of the use of animated film media in Akidah Akhlak learning in class II at MIN Demangan Kota Madiun namely before the implementation of learning, the teacher understands the applicable curriculum, especially about abilities or competencies that must be achieved after learning a learning material and adjusting the use of Syamil and Dodo animated films with material taught so that the results are maximum.